Fungi that benefit plants - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Small farmers could grow their own mycorrhizal inoculum, according to the International Center for Tropical Agriculture (CIAT) of Colombia. Mycorrhizal fungi grow in or on some plants' roots and can help that plant take up phosphates and water,...